The Recovery of Historical Buildings in Post-war Aleppo - Aboasfour, Yara; Nunes, Lígia (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Throughout history, wars and armed conflicts have severely impacted cultural heritage, erased collective memories, and left entire populations seemingly non-existent. However, recognizing the significance of cultural heritage is the primary impetus for its subsequent reconstruction. Since the Syrian war outbreak in 2011, Aleppo, one of the world’s oldest continuously inhabited urban centers, has suffered significant damage to its historic sites such as shrines, khans, and other architectural treasures due to bombings and clashes. In 2017, a study by the Directorate of Antiquities and Museums in Aleppo revealed that over 70% of the city’s historic center was destroyed. As a result, the cultural heritage of Aleppo and its social and symbolic values have been threatened. This represents a huge loss not only to Syria but also to the international community. This paper explores the significant role that collective memories play in shaping a city’s identity in the aftermath of war. The research aims to analyze the best approach for intervention during the reconstruction phase, whether it be preservation, restoration, enhancement, or eventual reconstruction by reviewing some international experiences. Furthermore, it explains the current situation of the old city of Aleppo and presents some cultural buildings that have been severely damaged or destroyed during the conflict. The study will compare the essential values of each case study and finally conclude with suggestions about the suitable intervention of different case studies that represent the values mentioned before.